Respiratory activity and physicochemical quality of juazeiro fruits (Ziziphus joazeiro Mart.) (Research, Society and Development, 2020)
The juazeiro (Ziziphus joazeiro Mart.) is a typical plant from Northeastern Brazil that has edible fruits, with sweet taste and rich in vitamin C. Some research is directed to the physical characterization of these fruits, however, little is known about the their respiratory nature. In this way, the objective was to evaluate the respiratory activity (CO2) and the physicochemical characteristics of juazeiro fruits in different stages of development. For this, fruits in five maturation stages (I, II, III, IV and V) were harvested from plants located at the Center for Science and Agri-Food Technology, at the Federal University of Campina Grande, Campus Pombal-PB, and evaluated according to titratable acidity, pH, soluble solids, ratio, ascorbic acid, total chlorophyll, total carotenoids and respiratory rate. The juazeiro fruits of stage IV maturation obtained low acidity, high levels of soluble solids and ascorbic acid. In the sensory and nutritional aspect, these characteristics are important for fresh consumption and processing. The respiratory rate increased with storage time for all stages of maturation. The fruits of stage IV maturation showed climacteric peak at 16 hours of storage, proposing that juazeiro fruits have a climacteric nature.